2015
DOI: 10.1158/1940-6207.capr-14-0336
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Breast Cancer Risk Biomarkers by High-Dose Omega-3 Fatty Acids: Phase II Pilot Study in Postmenopausal Women

Abstract: Higher intakes of the omega-3 eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) relative to the omega-6 arachidonic acid (AA) have been variably associated with reduced risk of premenopausal breast cancer. The purpose of this pilot trial was to assess feasibility and explore effects of high dose EPA and DHA on blood and benign breast tissue risk biomarkers prior to design of a placebo controlled Phase IIB trial. Premenopausal women with evidence of hyperplasia +/- atypia by baseline random periareolar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 77 publications
3
18
0
Order By: Relevance
“…Baseline and post-treatment RBC PUFA levels in EMT study participants were similar to those reported previously in studies of omega-3 PUFA supplementation in healthy volunteers [13,19], women with breast hyperplasia [20][21] and in patients with lung cancer [22]. In particular, post-treatment % RBC EPA values were similar to those observed in an eight-week study of exactly the same EPA-FFA formulation and dose in healthy volunteers and inflammatory bowel disease patients [23].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Baseline and post-treatment RBC PUFA levels in EMT study participants were similar to those reported previously in studies of omega-3 PUFA supplementation in healthy volunteers [13,19], women with breast hyperplasia [20][21] and in patients with lung cancer [22]. In particular, post-treatment % RBC EPA values were similar to those observed in an eight-week study of exactly the same EPA-FFA formulation and dose in healthy volunteers and inflammatory bowel disease patients [23].…”
Section: Discussionsupporting
confidence: 83%
“…Longer-term follow-up would have been required in order to confirm the return of the PUFA profile in RBCs to that observed pre-intervention. 'Washout' kinetics were not dependent on the prior degree of RBC incorporation or duration of EPA treatment and are similar (in these CRC patients) to the decay in RBC EPA content observed in at least three healthy volunteer studies, in which peak RBC EPA content was similar to that seen in the EMT study [13,19,27], as well as two more recent studies of pre-and post-menopausal women [20][21].…”
Section: Discussionsupporting
confidence: 76%
“…Fabian and colleagues conducted two parallel pilot studies to evaluate omega-3 supplementation in pre- and postmenopausal women at increased risk for breast cancer; individuals were treated for 6 months with combined EPA and DHA ethyl esters (3.4g/daily) and underwent pre-and post-treatment biopsies. [44, 46] While feasibility was the primary endpoint, secondary endpoints included several blood and tissue-based biomarkers evaluating changes in cytomorphology, Ki-67, circulating inflammatory and adipokine markers, RBC and tissue fatty acid composition, and targeted mRNAs, chemokines, and peptides. Treatment with combined EPA/DHA resulted in favorable modulation in certain tissue and circulating markers in both cohorts to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, these investigators demonstrated little to no change in breast levels of proinflammatory gene transcripts in response to combined EPA and DHA supplementation. [44, 46] In this setting, comparison of the studies by Fabian et al . to our study is limited by differences in study population, dose, duration and formulation of omega-3 supplementation, and study endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high dose omega-3 PUFAs supplementation (3,360 mg) over a six month period normalized adiponectin concentrations and decreased serum TNF-α and breast MCP-1 levels in postmenopausal women at risk of hyperplasia of the breast due to family history and/or an abnormal breast biopsy [67]. Omega-3 PUFA supplementation has also displayed potential in combating colon and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%